Tax Compliance: Respectful Treatment and Institutional Image - Dewi Prastiwi; I Made Narsa; Erlina Diamastuti (The Indonesian Accounting Review, 2021)
This study aims to analyze the effect of respectful treatment and institutional image on tax compliance. This study used a survey method of individual non-employee taxpayers at the Primary Tax Office (KPP) in the Regional Office of the DJP I, East Java, totaling 304 respondents. The data were analyzed using Structural Equation Modeling (SEM). The research findings showed that the strength of Crowding Theory and Trust Theory, and that the extrinsic intervention in the form of reward and punishment cannot always increase taxpayer compliance. Instead, a respectful approach and goodwill, ability and integrity of tax authorities in solving tax problems of taxpayers can increase tax compliance. This is supported by the results of the study that: 1) respectful treatment can improve institutional image; 2) respectful treatment can increase tax compliance; 3) institutional image can increase tax compliance. The implication of research results, respectful treatment of tax officers can be used to improve the image of the DJP and taxpayer compliance.